Educational Training on the Use Of Social Media as Digital Marketing at Selesa Coffee and Eatery - Ivana, Abigail Yoka; Pratiwi, Nuning Indah; Satria, Wahyu Indra (LPPM UIKA Bogor, 2024)
Selesa Coffee & Eatery, a café located at Jl. Tukad Batanghari No.12, Denpasar Selatan, Bali, faces significant challenges in optimizing their digital marketing strategy, particularly on social media platforms like Instagram. Despite offering a diverse menu and a comfortable atmosphere, their use of Instagram is suboptimal, with issues related to content quality and consistency. Unprofessional content and irregular posting frequency result in decreased engagement, limiting their potential to attract new customers and retain existing ones. Additionally, Instagram features such as Stories, IGTV, and Instagram Live are underutilized, and the lack of a well-planned strategy impedes their digital marketing effectiveness. To address these issues, it is crucial to enhance digital marketing education and training for employees. Research indicates that content consistency and quality are key to capturing audience attention and increasing brand awareness. By improving visual content quality, implementing a regular posting schedule, and effectively utilizing Instagram features, Selesa Coffee & Eatery can boost engagement and strengthen customer relationships. Furthermore, adopting a solid digital marketing strategy and leveraging analytics to measure campaign performance will aid in making more accurate and effective adjustments. Comprehensive digital marketing education and relevant practical experience are expected to enhance employee competence and support the café's growth in a competitive market.